Disposiç\~oes produtivas recentes: Uma aplicaç\~ao do modelo Shift-Share para os setores industriais na regi\~ao Centro-Oeste entre os anos de 2007 e 2014 - Murilo José de Souza Pires; Henrique Dantas Neder (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– From the 1980s to the present, transformations in the industrial structure of the states that make up the Midwest region drove industrial growth in this regional space. All of this was the result of a strategy to integrate this regional space into the national market and, from the 1990s, to international markets. Excess of raw material, proximity to consumer markets, tax incentives and benefits, public and private financing, labor in abundance, all of this played an important role in the increase of the industrial product of the Midwest. In this sense, the objective of this work is to describe the industrial structure of the Midwest region in what concerns the effects of the structural and differential components for the years 2007 to 2014. Therefore, the works of Rodrigo Sim\~oes, Jo\~ao Cerejeira e António de Matos highlight that the regions present sectorial differences in their industrial growth rates. Therefore, this paper will empirically test this evidence for the case of the states of the Midwest with the aim of verifying whether there is validity in this assertion. Roughly speaking, it is observed that the industrial sectors of Mato Grosso do Sul contributed positively to its industrial growth, as they presented a positive total net variation both for the structural component, as well as for the differential. Then came the industrial sectors of the state of Mato Grosso that contributed positively to the state's industrial growth, since the total net variation was positive, but with the structural component thinking positively and the differential component negatively. In the case of the state of Goiás, it can be seen that the industrial sectors that most contributed positively to industrial growth presented a positive total net variation, however, with the negative structural and differential components. And, finally, the industrial sectors of the Federal District that presented a positive total net variation , that is, that contributed, favorably, to the industrial growth of the state, in the period from 2007 to 2014, were those related to the structural component, to the whereas, the differential component did not have the strength to boost the industrial product of the Federal District above the national average.
Keywords: R11; 330; regional development; Midwest; shift-share model